Moderation of The Islamic Movement in Peace Implementation between The Government of The Republic of The Philippines and The Moro Nation in The South Philippines - Alwi, Fahrudin; Machmudi, Yon (Journal Of Middle East and Islamic Studies, 2022)
This study discusses the moderation of the Islamic movement in efforts to implement peace between the Government of the Republic of the Philippines and the Moro Nations in the southern Philippines. In this study, the authors use the Moderation Inclusion theory from Schwedler, the Social Movement theory from Sidney Tarrow, and the Wasathiyah Islamic theory. The authors will raise the actors who play a role in the Islamic movement and the factors that cause changes in the pattern of the movement. This research begins with an overview of the prolonged conflict that began with the arrival of the Spanish and Portuguese colonialists in the context of gold, glory, and gospel. The conflict continued after the independence of the Philippines in 1946. The economic gap to discrimination between Catholics in the northern Philippines and Muslims in the southern Philippines was one of the reasons for the continuing conflict. There were changes in the pattern of movements that occurred from the beginning fundamentally by taking up arms and turning into a diplomatic movement, at least caused by two main factors: first, about the paradigm shift that emerged from internal, and second, there was intervention from external, especially the international Islamic world.